1997
DOI: 10.1891/0047-2220.28.3.23
|View full text |Cite
|
Sign up to set email alerts
|

Client Rating of Counselor Effectiveness: A Call for Caution

Abstract: This study examined the relationship between client presession level of distress and client rating of the effectiveness of individual counseling sessions. Results of this investigation suggest a need for caution when interpreting client ratings of the effectiveness of counseling services. Preexisting client conditions may significantly influence the client ratings, independent of the effectiveness of the counselor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…They may have experienced their online exchanges as more challenging, tense, and uncomfortable as a result of the difficulty in emotionally connecting and working together with their more symptomatic clients (e.g., Zuroff et al 37 ). This finding is consistent with Jones and Markos' 18 finding that a higher client presession distress was related to lower ratings of session Smoothness.…”
Section: Client Social Support and Psychopathologysupporting
confidence: 91%
See 1 more Smart Citation
“…They may have experienced their online exchanges as more challenging, tense, and uncomfortable as a result of the difficulty in emotionally connecting and working together with their more symptomatic clients (e.g., Zuroff et al 37 ). This finding is consistent with Jones and Markos' 18 finding that a higher client presession distress was related to lower ratings of session Smoothness.…”
Section: Client Social Support and Psychopathologysupporting
confidence: 91%
“…Second, if online text therapy is comparable, then online clients and therapists should be moderated by participant factors in similar ways to face-to-face therapy. Our search of the face-to-face therapy literature identified four participant factors (personal or contextual characteristics) that could potentially influence text therapists' and text clients' impact and alliance ratings: therapists' theoretical orientation, 14,15 therapists' experience, 16,17 clients' symptom severity, 18 and clients' social support. 19 Based on these reports, we expected that therapists of more symptomatic clients would report lower Smoothness during their exchanges 18 ; moreexperienced therapist would report higher Partnership 20 ; less-experienced therapists would evaluate their exchanges as Deeper 16 ; and clients with more social support would report higher overall alliance ratings.…”
Section: Research Questions and Designmentioning
confidence: 99%
“…To test the study's hypotheses, I conducted a hierarchical multiple regression analysis by using racial and ethnic minority clients' satisfaction ratings (i.e., CSQ-8 scores) as the criterion variable. These clients' attitudes toward counseling were entered into the first step of the equation because previous researchers (e.g., Jones & Markos, 1997) have reported such attitudes to be associated with clients' ratings of counseling effectiveness. Their ratings of their counselors' general competence, as assessed by the CRF-S, were entered into the second step of the regression equation.…”
Section: Resultsmentioning
confidence: 99%
“…Because the acknowledgement of personal concerns may not necessarily cause some college students of color to seek mental health counseling (Davies et al, 2000; Lopez, Melendez, Sauer, Berger, & Wyssmann, 1998), it is feasible to consider that some students who ultimately seek professional psychological help will possess somewhat favorable attitudes about the efficacy of counseling and of counselors (Cramer, 1999). For instance, clients' presenting issues and attitudes have been found to significantly influence their ratings of the effectiveness of counseling services (Jones & Markos, 1997). Furthermore, it is likely that college students of color who positively rate the services they receive may also view their counselors favorably because of the salient roles that counselors play in the delivery of such services.…”
mentioning
confidence: 99%
“…She reported that, in general, she doesn't expect much from the mental health community because she perceives it as rigid even though people are supposed to be educated. Studies, such as Jones and Markos (1997), report that the initial attitude an individual holds about counseling may play a role in the perceived effectiveness of services. The client's actual motivation for change and the counselor's ability to form culturally sensitive and meaningful alliances with clients, however, may be more indicative of the factors contributing to client satisfaction with therapeutic services (Constantine, 2002).…”
Section: Hearing You Tell a Third Person How You Felt Like I Was Doinmentioning
confidence: 99%